Bahasa Perempuan dalam Novel Manjali Karya Ayu Utami: Analisis Wacana Kritis Perspektif Sara Mills - Andi Reski Ramadhani; Mahmudah Mahmudah; Faisal Faisal (INSIGHT: Indonesian Journal Social Studies and Humanities, 2023)
Abstract. This study aims to describe the form of female language in terms of (1) subject position, (2) object position, (3) reader position in Ayu Utami's novel Manjali using Sara Mills' Perspective Critical Discourse Analysis theory. This research is a qualitative descriptive research with critical discourse analysis theory from Sara Mills perspective. Source of research data is the novel Manjali by Ayu Utami. The research data are in the form of dialogue quotes, monologues and inner narratives as data sources. Data collection techniques using hermeneutic techniques, namely reading, note-taking and summarizing techniques. Data analysis was carried out by reducing data, presenting data and drawing conclusions.The results of this study indicate that there are 3 forms of female language. First, the form of female language is found based on the position of the subject Second, the form of female language is found based on the position of the object.Third, forms of female language are found based on the position of the reader through mediation processes and cultural code processes.Keywords: Critical Discourse Analysis; Women’s Language; Roman.